Preliminary exploration of the application of data governance in earthquake prevention and disaster reduction：A case study in Beijing - Yanan Chen; Tao Bo; Zhanying Wang; Jianjun Chang; Qingquan Tan; Weimin Jiang; Yun Dong (地震科学进展)
Data governance is of great significance in promoting the modernization of digital capabilities in China. This paper reviews the basic concepts of data governance and the evolution of data related policies in China, introduces the application of data governance technology in the field of natural disaster prevention and control, and analyzes the progress of data governance in the earthquake domain. Finally, based on survey results of Beijing’s earthquake prevention and disaster reduction data resources, this study proposes improvements for earthquake prevention and disaster reduction data governance work in Beijing and provides suggestions for future development.